Pengaruh Non Performing Financing (NPF) Terhadap Profitabilitas Bank Syariah di Indonesia - Edy Suprianto; Hendry Setiawan; Dedi Rusdi (Universitas Negeri Padang, 2020)
This study examines the effect of NPF on the profitability of Islamic banks in Indonesia. The research population is the whole of the research object to be examined. The population of this study is all Islamic commercial banks for the 2014-2018 period registered with Bank Indonesia. The sample was selected by purposive sampling method. The results of this study indicate that NPF has a negative effect on the profitability of Islamic banks in Indonesia.Keywords: NPF, Profitability, and Syari’ah Bank.